From rolling stones to rolling reefs: a Devonian example of highly diverse macroids. (19th June 2018) - Denayer, Julien
Abstract : The upper carbonate member of the Aisemont Formation (Upper Frasnian, Belgium) yielded a surprisingly diverse assemblage of macroids varying in size, shape and composition, from simplest microbial oncoid to complex, polytaxic circumrotatory macroid. A descriptive classification combining composition and geometry of macroids is proposed. It suits for sedimentological and palaeobiological analyses. Five categories forming a continuum are distinguished as follows: (1) simple oncoids, consisting of microbial coating of various nuclei; (2) composite oncoids, involving several encrusting taxa and microbes‐induced precipitates; (3) simple circumrotatory macroids, constructed by one or few different organisms and forming free‐rolling particle; (4) polytaxic circumrotatory macroids, constructed by diverse organisms, usually in sequential coating and form free‐rolling object; and, (5) polytaxic domed macroids, polytaxic assemblage of encrusting organism forming domed or columnar anchored bioconstructions. The dominant (in number and volume) encrusting organisms are the tabulate corals and stromatoporoids that both possessed the ability to attach to any hard substrate. Microbes also contributed to the formation of macroids although the volume they occupy is relatively limited. Skeletal invertebrates likely grew during the good season when environmental conditions were suitable for the growth, then partly or totally died and was colonized by microbes during the bad season. The surface of the macroid (after rolling or not) was subsequently re‐coated with skeletal organisms when suitable conditions re‐established. Final burial of the macroid occurred during the good season as their outermost surface is rarely coated with microbes. Geopetal sediment filling of cavities displays various directions indicating the rolling of the objects during their formation. Periodical rolling or tilting may be related to seasonal storms and the resulting assemblage formed genuine rolling reefs of crucial importance for birth palaeoecological and sedimentological analysis.